The bidirectional association among female hormone‐related cancers: breast, ovary, and uterine corpus - Min‐Chi Chen; Kuan‐Der Lee; Chang‐Hsien Lu; Ting‐Yao Wang; Shih‐Hao Huang; Chao‐Yu Chen (Cancer Medicine)
Abstract Breast, ovarian, and uterine corpus cancers are common female cancers and categorized as hormone‐related diseases. Previous studies reported a unidirectional relationship for each cancer, but few studied the reciprocal association in the same cohort. A population‐based study was carried out in Taiwan to test the hypothesis that there are pairwise bidirectional associations among these cancers. Using the same cohort of 110,112 cases with primary female cancers including uterine corpus cancer (11,146 cases), ovarian cancer (12,139 cases), or breast cancer (86,827 cases) from the Taiwan Cancer Registry from 1979 to 2008, the pairwise risks of second cancer among uterine corpus, ovary, and breast cancer cases were evaluated by standardized incidence ratios (SIRs) and the corresponding 95% confidence intervals (CIs) to quantify the excess of second malignancies. A reciprocal relationship was found for these three female cancers, particularly most prominent between uterine and ovarian cancers, followed by breast and uterine cancers as well as breast and ovarian cancers. The overall risk of second cancers was highest within the first 5 years after the diagnosis of primary cancer. The bidirectional relationships suggest common risk factors among these three female cancers. This is the largest cohort study to focus on the bidirectional associations among hormone‐related cancers in Asian women, and these results could aid in the development of early prevention strategies and follow‐up surveillance programs.